First day performance of private equity backed IPO of chinese firms. - Lee, King Fei. (2008)
This report identifies the possible aspects that would have an effect on the Initial Public Offerings (IPOs) first day performance. It covers the analysis of various factors affecting the performance of Private Equity (PE)- backed IPOs of Chinese firms.